Capturing patient-reported outcomes: paper versus electronic survey administration. Issue 3 (8th September 2022) - Nguyen, Mai P.; Rivard, Rachael L.; Blaschke, Breanna; Vang, Sandy; Schroder, Lisa K.; Cole, Peter A.; Cunningham, Brian P.
Abstract : Abstract: Objective: To compare the capture rates and costs of paper patient-reported outcomes (pPRO) administered in-clinic and electronic PROs (ePRO) collected through emails and texts. Design: Retrospective review. Setting: Level 1 trauma center. Patients/Participants: The pPRO program enrolled 2164 patients for postsurgical follow-up in 4 fracture types: ankle, distal radius, proximal humerus, and implant removal from 2012 to 2017. The ePRO program enrolled 3096 patients in 13 fracture types from 2018 to 2020. Among the patients enrolled in the ePRO program, 1296 patients were matched to the 4 original fracture types and time points. Main Outcome Measures: PRO capture rates in 4 fracture types by matched time point and estimated cost of each program per enrolled patient. Results: At first follow-up, pPRO provided a higher capture rate than ePRO for 3 of 4 fracture types except for implant removal ( P < 0.05). However, at 6-month and 1-year follow-ups, ePRO demonstrated statistically significant higher capture rates when compared with pPRO for all applicable modules ( P < 0.05). The average cost for the pPRO program was $171 per patient versus $56 per patient in the ePRO program. Patients were 1.19 times more likely to complete ePRO compared with pPRO ( P = 0.007) after controlling for age, sex, fracture type, and time point. Conclusion: The electronic PRO service has improved long-term capture rates compared with paper PROs, while minimizing cost. A combined program that includes both in-clinic and out of clinic effort may be the ideal model for collection of PROs. Level of Evidence: Level 3.